«THINKING ABOUT POETRY»: THE SHARED POETICS BETWEEN MAGDA PORTAL AND SERAFIN DELMAR - Morales Isla, María de los Angeles (2018)
Two Peruvian poets, belonging to the avant-garde period, present a similar poetic and at the same time differentiated conception: Magda Portal and Serafin Delmar. Both poets reflect on the poetic construction and the creative process. It is a bet to give poetry a form of knowledge, that is, a cognitive capacity. Thus, the poem is irreverent and affects language, emphasizes its silence. A comparative interpretation of A Hope and the Sea (1927) by Portal and Radiographs of the Pacific (1927) by Delmar demonstrates structural similarities, as well as the urgency of reflecting on poetry in the face of the vicissitudes of the early twentieth century.